Microsoft Office 2013 try it! - Parsons, June Jamrich; Oja, Dan; Mulder, Donna (Practical series, 2015)
This book will provide coverage on Microsoft Word, Excel, Access, and PowerPoint 2013 and extensive end-of-chapter Projects on key topics in each application. There are also Capstone Projects for Word, Excel and PowerPoint: Word: 10 projects, including 1 capstone; Excel: 8 projects, including 1 capstone; Access: 10 projects; PowerPoint: 9 projects, including 1 capstoneked